Excitation-dependent fluorescence from atomic/molecular layer deposited sodium-uracil thin films - Ville Pale (Nature Portfolio, 2017)
Abstract Atomic/molecular layer deposition (ALD/MLD) offers unique possibilities in the fabrication of inorganic-organic thin films with novel functionalities. Especially, incorporating nucleobases in the thin-film structures could open new avenues in the development of bio-electronic and photonic devices. Here we report an intense blue and widely excitation-dependent fluorescence in the visible region for ALD/MLD fabricated sodium-uracil thin films, where the crystalline network is formed from hydrogen-bonded uracil molecules linked via Na atoms. The excitation-dependent fluorescence is caused by the red-edge excitation shift (REES) effect taking place in the red-edge of the absorption spectrum, where the spectral relaxation occurs in continuous manner as demonstrated by the time-resolved measurements.